Effect of Nutrient Availability on Progenitor Cells in Zebrafish (Danio Rerio). Issue 1 (15th June 2016) - Benítez‐Santana, Tibiábin; Simion, Matthieu; Corraze, Geneviève; Médale, Françoise; Joly, Jean‐Stéphane
Abstract: In zebrafish brains, populations of continuously proliferating cells are present during an entire life span. Under normal conditions, stem cells give rise to rapidly proliferating progenitors that quickly exit the cell cycle and differentiate. Hence fish are favorable models to study what regulates postembryonic neurogenesis. The aim of this study was to determine if optic tectum (OT) cell proliferation is halted during nutritional deprivation (ND) and whether or not it can be restored with refeeding. We examined the effect of ND on the proliferation of Neuroepithelial/Ependymal Progenitor cell (NeEPC) and transitory‐amplifying progenitors (TAPs). Following ND, no PCNA immunostaining was found in OT of starved fish, while positive cell populations of PCNA positive progenitors are found at its periphery in control fish. This indicated that active proliferation stopped. To label retaining progenitor cells, BrdU was applied and a chase‐period was accompanied by ND. Positive NeEPCs were detected in the external tectum marginal zone of starved fish suggesting that these progenitors are relatively immune to ND. Moreover in the internal tectum marginal zone labeled retaining cells were observed leaving the possibility that some arrested TAPs were present to readily restart proliferation when nutrition was returned. Our results suggest that neurogenesis was maintained during ND and that a normal proliferative situation was recovered after refeeding. We point to the mTOR pathway as a necessary pathway in progenitors to regulate their mitosis activity. Thus, this study highlights mechanisms involved in neural stem and progenitor cell homeostatic maintenance in an adverse situation. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 26–38, 2017